Prosperity Gospel and the Crisis of Authenticity: Challenges Facing Pentecostal and Charismatic Movements in Africa - Clement Chinkambako Abenguni Majawa (Journal of Religious and Socio-Cultural, 2026)
The rapid growth of Pentecostal and Charismatic movements across Africa has brought renewed spiritual energy to millions of believers, yet this expansion has also generated significant challenges related to authenticity, abuse of pneumatic gifts, and the distortion of the Gospel message. This article examines the major challenges facing Pentecostal and Charismatic Christianity in Africa, including the proliferation of the prosperity gospel, the misuse of spiritual gifts for personal gain, the rise of false prophets and televangelists who exploit vulnerable populations, and the growing tensions between Catholic Charismatic Renewal and independent Pentecostal churches. Drawing from theological analysis, ecclesial documents, and contemporary case studies from Kenya, Malawi, Nigeria, Ghana, and South Africa, the article argues that the crisis of authenticity in African Pentecostalism stems from a lack of proper discernment, inadequate ecclesiastical oversight, and the prioritization of material wealth over spiritual transformation. The research employs a qualitative, document-based theological method, analyzing primary sources (magisterial documents, pastoral letters) and secondary sources (scholarly literature, media reports) to identify recurrent patterns of abuse and to propose a framework for discernment. This research makes two original contributions to the scholarly discourse. First, it provides a systematic theological critique of prosperity theology as it manifests in African contexts, distinguishing legitimate material blessing from abusive exploitation. Second, it proposes a five-criteria framework for discernment rooted in Catholic magisterial teaching, offering practical guidance for pastors, bishops, and lay leaders to evaluate charismatic claims and restore integrity to Pentecostal witness in Africa.